PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN IPA KELAS VIII MADRASAH TSANAWIYAH SINOA - Kiki Reski Amalia; Abd Haling; Sella Mawarni; Ainun Mardiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and test the practicality of interactive learning multimedia based on Smart Apps Creator (SAC) in supporting students' understanding of science learning in class VIII MTs Sinoa, especially on vibration, wave, and light materials. The research method used is Research and Development (R&D) with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. At the validation stage, the results from material experts and media experts showed that the developed learning multimedia was very valid with a material validity level of 95.8% and a media validity of 100%. This shows that the content and design of the learning media are very much in accordance with the standards needed to improve student understanding. This validation provides confidence that the material presented in the SAC application has met the eligibility criteria for use in the science learning process. Furthermore, at the practicality testing stage, the responses of educators and students to this learning multimedia showed very positive results. The response of educators to the practicality of this media reached 95.4%, while the response of students was 90.5%. This indicates that both educators and students feel that this media is very practical to use in learning, so that it can increase student interaction and involvement during the learning process. The implementation of media in learning resulted in higher enthusiasm among students, and the evaluation results showed a significant increase in student understanding. Thus, the use of interactive learning multimedia based on SAC has proven to be an effective alternative innovative media in improving student understanding at MTs Sinoa.